Implementation of the Use of Force by Police Officers In Handling Mass Actions Based On The Regulation of The Chief of The Indonesian National Police Number 1 of 2009 - Jaftoran, Allan Fredrik; Siswani, Carina Budi; Hammar, Imanuel I.R. (LEGAL BRIEF, 2025)
This study examines the implementation of the use of force by Indonesian National Police (Polri) officers in handling mass demonstrations, focusing on the application of Regulation of the Chief of the Indonesian National Police Number 1 of 2009. Using a normative juridical method, the research analyzes statutory provisions, legal doctrines, and selected empirical cases from West Papua to assess compliance with the principles of legality, necessity, proportionality, and accountability. The findings indicate that, although the regulatory framework has formally adopted international human rights standards and a graduated use-of-force model, significant gaps persist between normative rules and operational practice. In several documented incidents, coercive measures such as tear gas, rubber bullets, and mass arrests were applied prematurely, without sufficient de-escalation efforts or transparent post-action accountability. These shortcomings are influenced by structural weaknesses in internal oversight, limited professional training, and an institutional culture that prioritizes security over dialogue-based policing. The study concludes that strengthening external oversight mechanisms, enhancing human rights-based training, and reforming organizational culture are essential to align police practices with democratic principles and international standards on the use of force